2021
DOI: 10.3130/aijs.86.706
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Vibration Characteristics of a Seismically-Isolated Building Constructed on an Inclined Bearing Layer Inferred From Recorded Motions and Response Analyses

Abstract: In this paper, torsional vibration characteristics of a seismically-isolated building constructed on an inclined bearing layer are investigated based on strong motion records and microtremor measurements. In order to elucidate the generation mechanism of torsional vibration, the torsional response of the building was reproduced using a 3D-frame model of the building and a 2D-FEM model of the subsurface structure. It is found that several types of torsional vibrations were generated in different frequency range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Generally, composite foundations and pile foundations with piles of different lengths are adopted as the foundation type of structures built on sloping bedrock. The seismic response characteristics of such structures are typically investigated using analyses of earthquake damage, [11][12][13] seismic observations of actual buildings, [14][15][16] model shaking table tests in a centrifugal field, [17][18][19] and 3D finite element analysis (FEA). 12,14,[17][18][19][20][21][22][23][24] In addition, studies have demonstrated that these characteristics are affected by the input motion from an irregular sedimentary layer and the constraints of the pile tip.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, composite foundations and pile foundations with piles of different lengths are adopted as the foundation type of structures built on sloping bedrock. The seismic response characteristics of such structures are typically investigated using analyses of earthquake damage, [11][12][13] seismic observations of actual buildings, [14][15][16] model shaking table tests in a centrifugal field, [17][18][19] and 3D finite element analysis (FEA). 12,14,[17][18][19][20][21][22][23][24] In addition, studies have demonstrated that these characteristics are affected by the input motion from an irregular sedimentary layer and the constraints of the pile tip.…”
Section: Introductionmentioning
confidence: 99%